ANALISIS PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP MINAT BELAJAR FISIKA SISWA KELAS X SMAN 1 MUARO JAMBI - Resnalia .; Maison .; Dwi Agus Kurniawan (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT The research was conducted to find out where the media learning influence on student learning interest. The research population was 30 class X students at SMAN 1 Muaro Jambi. Physics is a lesson that is considered difficult for students, especially students, the development of technology can also help the development of learning media, learning interest can also determine Hassil learning students this is underlying researchers to conduct research. Where the type of research used by researchers is descriptive quantitative research with data collection methods, namely using a questionnaire survey with a number of 2 questionnaires, where the questionnaire used is related to learning interest and also the use of learning media. From the results of the questionnaire that has been distributed, the researcher conducts data analysis by conducting a regression test to find out where the use of learning media on student learning interests where the results obtained the significance value of the regression test of both data can we know that the significance value .154 Where the significance value is 0.0 Because of the SIG value> α or 0.154> 0.05, it was concluded that there was an influence between learning media to the learning interest in class X students at SMAN 1 Muaro Jambi. Keywords: Interest in Learning, Learning Media, Physics